A Powder on the move - Wirth, Karl-Ernst; Linsenbühler, Markus (European Coatings Journal, 2002)
There is a rising demand on powder coatings towards ever finer particles. However, such fine powders are more difficult to fluidise. This problem can be overcome by coating the powder coating particles themselves with spacer-nanoparticles, thus reducing the attractive van der Waals forces. Here, an innovative process for this particle coating is presented: The spacer particles and powder coating particles are given opposite electric charges and then mixed - both in a medium of liquid nitrogen. The procedure is promising also as a general method for mixing fine solid powders as well.
UnivIS-Import:2015-03-09:Pub.2002.tech.ITC.mechve.apowde
Keywords: powder; technology